The economic contribution of Colorado's wine industry - Kress, George, author; Thilmany, Dawn, author; Colorado State University, publisher (Colorado State University. Libraries, 2005)
This study provides a brief overview of the economic role of the wine industry in Colorado, with some integration of a similar report focused on the primary wine growing area, Mesa County. After presenting underlying sales and production data, an estimate ofthe wine industry's economic contribution to Colorado is presented.
Project leaders, George Kress, Dawn Thilmany.
Keywords: Wine industry -- Economic aspects -- Colorado